Battery separator, anode, energy galvanic cell and method for preventing lithium deposition
Through improved porous battery separator and specific material design, the problems of lithium deposition and dendrites in lithium-ion batteries are solved, and the stability of lithium deposition and battery at high temperatures is achieved at high charging rates, which extends the battery life and Improved performance.
Patent Information
- Application Number
- CN202411317538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-03-20
- Filing Date
- 2018-03-19
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium deposition in lithium ion batteries can lead to serious safety problems such as thermal events and explosions, especially at high charging rates. The prior art is difficult to effectively prevent lithium deposition and dendrites from growing, while the battery is prone to melting at high temperatures.
Adopt an improved battery separator with a porous structure and filled with ion-conducting medium, with the characteristics of no volume, high mechanical strength, electrical insulation, no reaction with electrodes, preventing dendrites from growing, and does not melt at high temperatures, combined with specific anodes and cathode material design to ensure that lithium deposition does not occur at high charging rates.
Extend battery life, reduce faults and lithium deposition, maintain charging and discharge rates, improve battery performance, ensure safety and stability.
Smart Images

Figure CN119208922A_ABST
Abstract
Description
[0001] This application is a divisional application. The priority date of the original PCT application is March 20, 2017; the original international application date is March 19, 2018; the original international application number is PCT / US2018 / 023107; the date of entering the Chinese national phase is November 15, 2019, and the Chinese application number is 201880032347.0; the original invention name is "Improved battery separators, electrodes, primary cells, lithium batteries and related methods".
[0002] Priority declaration
[0003] This application claims the benefit of and priority under 35 U.S.C. §119(e)(1) to U.S. Provisional Patent Application No. 62 / 473,596, filed on March 20, 2017. The entire contents of this U.S. Provisional Patent Application are incorporated herein by reference. Technical Field
[0004] According to at least selected embodiments, the present disclosure or invention is directed to new or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, manufacturing and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems and / or the like for lithium batteries (especially secondary lithium batteries, such as secondary lithium ion batteries) and / or CE, ESS and / or EDV batteries. According to at least specific embodiments, the present disclosure or invention is directed to new or improved methods of observing or defining tortuosity, porosity, lithium deposition and galvanic cell design using such new ideas, definitions and / or data. In addition, disclosed herein are methods, systems and battery components for extending battery life, reducing battery failures, reducing dendrites, reducing lithium deposition, maintaining charge and discharge rates, improving configuration, improving performance and / or the like. Background Art
[0005] There is a need, among other things, for improved battery separators, particularly lithium-ion battery separators, that resist dendrite formation and do not melt even at high temperatures.
[0006] In lithium-ion batteries, carbonaceous materials are generally used as anode materials for lithium-ion batteries. Although carbonaceous materials have high energy density, the charge and discharge voltages are very close to the voltage of lithium deposition. Therefore, lithium deposition may occur due to overvoltage, especially at high charging rates, which can cause large polarization. The deposition of lithium metal within the battery can cause serious safety issues, which may lead to thermal events, runaway or explosion. Therefore, there is a need for lithium-ion batteries or primary cells that do not undergo lithium deposition even at high charging rates. SUMMARY OF THE INVENTION
[0008] According to at least selected embodiments, the present disclosure or invention may address the above needs, issues or problems; and / or it is directed to new or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, manufacturing and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems, and / or the like for lithium batteries, especially secondary lithium batteries, such as secondary lithium ion batteries and / or CE, ESS and / or EDV batteries. According to at least specific embodiments, the present disclosure or invention is directed to new or improved methods of observing or defining tortuosity, porosity, lithium deposition and galvanic cell design using such new ideas, definitions and / or data. In addition, disclosed herein are methods, systems and battery components for extending battery life, reducing battery failures, reducing dendrites, reducing lithium deposition, maintaining charge and discharge rates, improving configuration, improving performance and / or the like.
[0009] In one aspect, the present application is directed to an improved battery separator. This improved separator has at least one of the following characteristics when wetted by electrolyte: no volume or small volume; no mass or light mass; absorbs as much liquid electrolyte as possible; blocks or removes any harmful substances in the electrolyte; does not melt at any high temperature; does not react with the cathode or anode under any conditions; has a mechanical strength equal to or greater than steel; is an electrical insulator under any circumstances; prevents the growth of metal dendrites. In some embodiments, the separator has 1 or more of the aforementioned characteristics. In some embodiments, the separator has 2 or more of the aforementioned characteristics. In some embodiments, the separator has 3 or more of the aforementioned characteristics. In some embodiments, the separator has 4 or more of the aforementioned characteristics. In some embodiments, the separator has 5 or more of the aforementioned characteristics. In some embodiments, the separator has 6 or more of the aforementioned characteristics. In some embodiments, the separator has 7 or more of the aforementioned characteristics. In some embodiments, the separator has 8 or more of the aforementioned characteristics. In some embodiments, the separator has all 9 of the aforementioned characteristics or at least all 9 of the aforementioned characteristics.
[0010] In some embodiments, the battery separator described herein is a porous, microporous or nanoporous battery separator, and the pores of the battery separator are filled with an ionically conductive medium. In some embodiments, the battery separator whose pores are filled with an ionically conductive medium conducts lithium ions when it is dry (no electrolyte added), when it is wetted with an electrolyte, or in this case when it is dry (no electrolyte added) and when it is wetted with an electrolyte.
[0011] On the other hand, an energy cell can be used at a current greater than or equal to 3.0C (1C = 2.3 mA / cm 2) without lithium deposition. In some embodiments, the primary cell can be charged at a charge rate greater than or equal to 3.5C, greater than or equal to 4.0C, greater than or equal to 4.5C, or greater than or equal to 3.0C but less than 5.0C.
[0012] The energy cell includes at least the following: an anode containing lithium; and a cathode.
[0013] In some embodiments, the lithium-containing anode has a thickness from about 50 to about 200 microns. The thickness may also be from about 60 to about 200 microns or about 60 to about 125 microns. In some embodiments, the porosity of the anode may be greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 40%. In some embodiments, the anode porosity may be greater than or equal to 15% but less than or equal to 50%. In some embodiments, the curvature of the anode may be less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2. In some embodiments, the curvature is between 1.0 and 2.0, preferably between 1.2 and 2.0. Even more preferably, the curvature of the anode may be greater than or equal to 1.2 but less than or equal to 1.3.
[0014] In some embodiments, the lithium-containing anode is selected from lithium cobalt oxide (LCO); lithium manganese oxide (LMO); lithium iron phosphate (LFP);
[0015] [Li(Ni x Mn y Co z )O2], where 0.33>x>0.9 and x+y+z=1; NCA[Li(Ni x Co y Al z )O2], wherein 0.8>x>0.9 and x+y+z=1; and at least one material selected from a combination thereof.
[0016] In some embodiments, the cathode of the energy cell has a thickness of from about 50 to about 200 microns, from about 75 to about 200 microns, or from about 75 to about 150 microns. In some embodiments, the porosity of the cathode may be greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 10%, but less than 40%. In some embodiments, the curvature of the cathode may be less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2. In some preferred embodiments, the curvature of the cathode may be greater than or equal to 1.0 but less than or equal to 2.0. Even more preferably, the curvature of the cathode may be greater than or equal to 1.2 but less than or equal to 1.5.
[0017] In some embodiments, the cathode of the energy cell may be made of at least one material selected from the group consisting of natural graphite, artificial graphite, amorphous carbon, alloys containing tin and / or silicon, spinel lithium titanium oxide, and combinations thereof.
[0018] Further, in addition to the anode and cathode containing lithium, the energy cell described herein may also include an electrolyte. The electrolyte may be selected from: ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC) and combinations thereof. In some embodiments, the electrolyte may include an electrolyte additive.
[0019] In some further embodiments, the energy cells described herein may include a separator, including the improved separators described herein. For example, the energy cell may include a lithium-containing anode, a cathode, and a separator. In some other embodiments, the energy cell may include a lithium-containing anode, a cathode, an electrolyte, and a separator.
[0020] In some embodiments, the energy cell may be a primary or secondary energy cell.
[0021] On the other hand, an anode containing lithium is described herein. Anodes containing lithium can be used in energy cells described herein. In some embodiments, the anode containing lithium has a thickness from about 50 to about 200 microns. The thickness can also be from about 60 to about 200 microns, or about 60 to about 125 microns. In some embodiments, the porosity of the anode may be greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 40%. In some embodiments, the porosity of the anode may be greater than or equal to 15%, but less than or equal to 50%. In some embodiments, the anode curvature may be less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2. In some embodiments, the curvature is between 1.0 and 2.0, preferably between 1.2 and 2.0. Even more preferably, the anode curvature may be greater than or equal to 1.2, but less than or equal to 1.3.
[0022] In some embodiments, the lithium-containing anode is made of at least one material selected from the group consisting of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), [Li(Ni x Mn y Co z )O2] (where 0.33>x>0.9 and x+y+z=1), NCA[Li(Ni x Co y Al z)O2](wherein 0.8>x>0.9 and x+y+z=1), and combinations thereof.
[0023] In some embodiments, the void space in the cathode may contain an ionically conductive medium.
[0024] On the other hand, a cathode that can be used in the energy cell described herein is disclosed. In some embodiments, the cathode has a thickness from about 50 to about 200 microns, from about 75 to about 200 microns, or from about 75 to about 150 microns. In some embodiments, the porosity of the cathode may be greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 10%, but less than 40%. In some embodiments, the curvature of the cathode may be less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2. In some preferred embodiments, the cathode curvature may be greater than or equal to 1.0, but less than or equal to 2.0. Even more preferably, the cathode curvature may be greater than or equal to 1.2, but less than or equal to 1.5.
[0025] In some embodiments, the cathode may be made of at least one material selected from the group consisting of natural graphite, artificial graphite, amorphous carbon, an alloy containing tin and / or silicon, spinel lithium titanium oxide, and combinations thereof.
[0026] In some embodiments, the void space of the cathode may contain an ionically conductive medium (ICM). BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Ion transport, tortuosity, and Gurley (permeability) are depicted.
[0028] Figure 2 Ion transport and tortuosity are depicted.
[0029] Figure 3 Depicted are exemplary lithium-ion primary cell design principles.
[0030] Figure 4 Depicted is the polarization of a lithium-ion battery.
[0031] Figure 5 is a graphical representation of the lithium concentration in the electrode particles after high current discharge.
[0032] Figure 6 The electrochemical model, thermal model, and chemical model are depicted.
[0033] Figure 7 The basic electrochemical equation is depicted.
[0034] Figure 8A review of the potentials of lithium ions during equilibrium, charge, and discharge is depicted.
[0035] Fig. 9 This is a graph of lithium concentration distribution in a porous lithium-ion primary battery that 100% follows Faraday's reaction law.
[0036] Fig.10 Included are graphs showing the lithium concentration in the electrolyte upon charge and discharge.
[0037] Fig.11 Included is a curve and a partially enlarged view of the curve, showing the drop in cathode potential during discharge.
[0038] Fig.12 Included is a curve and a magnified portion of the curve showing the increase in anode potential during 4C discharge.
[0039] Fig.13 Included are two graphs showing the drop in electrode potential at the anode upon 4C charging.
[0040] Fig.14 Included is a curve and a portion of the curve showing the anode potential drop during 4C charging.
[0041] Fig.15 Included is a curve and a partially enlarged view of the curve, showing the increase in cathode potential during 4C charging.
[0042] Fig.16 Included is a graph from a DCIR measurement showing the variation of the cell voltage over time.
[0043] Fig.17 Included are two graphs plotting the relationship between potential (V) / SOC and thickness x (m) for electrodes with two different thicknesses of 1X and 2X in the initial state (t=0).
[0044] Fig.18 Included are two graphs showing the relationship between potential (V) / SOC and thickness x (m) for electrodes with two different thicknesses in a dynamic state (t>0).
[0045] Fig.19 is a graph showing when Li deposition starts when different charging rates are applied to electrodes with different thicknesses.
[0046] Fig. 20 is a graph showing when Li deposition starts when different charging rates are applied to electrodes with different porosity values.
[0047] Fig.21is a graph showing when Li deposition starts when different charging rates are applied to electrodes with different tortuosity values.
[0048] Fig. 22 is a graph including baseline cell parameters for a cell without Li deposition. DETAILED DESCRIPTION
[0049] The embodiments described herein may be more easily understood by reference to the following detailed description of the invention, examples and figures. However, the elements, devices and methods described herein are not limited to the specific embodiments presented in the detailed description of the invention, examples and figures. It should be appreciated that these embodiments are merely illustrations of the principles of the invention. Various changes and adjustments are apparent to those skilled in the art without departing from the spirit and scope of the invention.
[0050] In addition, all ranges disclosed herein should be understood to encompass any and all subranges contained therein. For example, the stated range "1.0 to 10.0" should be considered to include any and all subranges starting with a minimum value of 1.0 or greater and ending with a maximum value of 10.0 or less, such as 1.0 to 5.3 or 4.7 to 10.0 or 3.6 to 7.9.
[0051] Unless otherwise expressly stated, all ranges disclosed herein should also be considered to include the endpoints of the range. For example, a range of "between 5 and 10", "from 5 to 10" or "5-10" should generally be considered to include endpoints 5 and 10.
[0052] Further, when the phrase "up to" is used in connection with a quantity or amount, it should be understood that the quantity is at least a detectable quantity or amount. For example, a material present in an amount "up to" a specific amount may be present from a detectable amount up to and including the specific amount.
[0053] According to at least selected embodiments, described herein are improved battery separators, improved energy cells (which optionally include the improved battery separators), and / or improved anodes and cathodes (which optionally are used in conjunction with the improved battery separators or improved energy cells described herein.
[0054] Battery separator
[0055] Unless otherwise described in a specific embodiment, there are not many limitations on the membranes or battery separators described herein. In some embodiments, the battery separator can be an improved battery separator comprising a porous membrane, which has at least one of the following properties when wetted by an electrolyte: no volume or small volume; no mass or light mass; absorbs as much liquid electrolyte as possible; blocks or removes any harmful substances in the electrolyte; does not melt at any high temperature; does not react with the cathode or anode under any conditions; has a mechanical strength equal to or greater than that of steel; is an electrical insulator (no electronic conduction) under any circumstances; and prevents the growth of metal dendrites.
[0056] One way to impart some of the aforementioned properties is to add ceramics to the battery separator. For example, in some embodiments, a ceramic coating can be applied to one or more surfaces of a porous membrane that is part of a battery separator. In some embodiments, a ceramic material can be added to a microporous membrane. For example, if the membrane is made of a material such as If the ceramic material is formed by a dry process (forming micropores by direct stretching rather than using solvent to extract the pore-forming substance; the precursor does not contain any fillers, additives or plasticizers), the ceramic material can be extruded together with the polymer (e.g., polyolefin polymer) used to form the membrane (co-extruded ceramic coating). In some embodiments, if the membrane is formed by, for example, In a multilayer film formed by a dry process such as a dry stretch process, the ceramic material may be present in only some layers and not in other layers. The ceramic material may be added to some layers and not to other layers by extruding the ceramic material with the polymer used to form some layers but not with the polymer used to form other layers.
[0057] Many ceramics can even conduct ions better than liquids. See, for example, US6,432,586, the entire contents of which are incorporated herein by reference. Ceramics can also block or remove harmful substances in the electrolyte. Ceramics do not melt at very high temperatures and, in most cases, do not react with most anode or cathode materials. Ceramics can be mechanically strong. Therefore, ceramics are a preferred material for providing some of the properties of the improved battery separator described herein.
[0058] porous membrane
[0059] Unless otherwise described in a particular embodiment, there are no too many limitations on the porous membrane described herein. It can be nanoporous, microporous or macroporous. In some preferred embodiments, the porous membrane is microporous.
[0060] As used herein, microporous means that the membrane contains micropores or micron-sized pores. In some embodiments, the average pore size of the microporous membrane is less than 2 microns, and in preferred embodiments, the average pore size is less than 1 micron. In some embodiments, the average pore size is between 0.01 and 1 micron, preferably between 0.01 and 0.08 microns, more preferably between 0.01 and 0.06 microns, and in some embodiments, from 0.01 to 0.04, from 0.01 to 0.03, or from 0.1 to 0.02 microns.
[0061] In some preferred embodiments, the microporous membrane itself, for example without any coating such as a ceramic coating thereon, has a thickness ranging from 2 to 50 microns, from 4 to 40 microns, from 4 to 30 microns, from 4 to 20 microns, from 4 to 10 microns, or less than 10 microns. The thickness can be measured in microns (μm) using an Emveco Microgage 210-A micrometer thickness gauge and ASTM D374 test procedures. Thin microporous membranes are preferred for certain applications. For example, when used as a battery separator, a thinner separator membrane allows more anode and cathode materials to be used in the battery, thereby obtaining a battery with higher energy and higher power density.
[0062] In some preferred embodiments, the microporous membrane has a porosity (e.g., surface porosity) of about 40 to about 70%, sometimes about 40 to about 65%, sometimes about 40 to about 60%, sometimes about 40 to about 55%, sometimes about 40% to about 50%, sometimes about 40% to about 45%, and so on. In some embodiments, the porosity can be higher than 70% or lower than 40% if a particular application is desired, but the range of 40 to 70% is a working range for battery separators, which is one way in which the disclosed microporous membranes can be used. Porosity is measured using ASTM D-2873 and is defined as the percentage of void space (e.g., pores) in one area of the microporous membrane measured in the machine direction (MD) and transverse direction (TD) of the substrate.
[0063] In some preferred embodiments, the microporous membrane may have a JIS Gurley varying from 50 to 300, 75 to 300, and or 100 to 300. However, unless otherwise specified in a particular embodiment, there is not much restriction on the JIS Gurley value, and higher (e.g., higher than 300) or lower (e.g., lower than 50), JIS Gurley values may be required for different purposes. In this article, Gurley is defined as the Japanese Industrial Standard (JIS Gurley) and is measured using an OHKEN permeability tester in this article. JIS Gurley is defined as the time in seconds required for 100cc of air to pass through a square inch of film at a constant pressure of 4.9 inches of water.
[0064] The microporous membrane can be made in any manner not inconsistent with the objectives described herein. For example, in some preferred embodiments, the microporous membrane is a dry process microporous membrane, meaning that the membrane is formed without the use of a solvent. An exemplary dry process is a dry stretching process comprising, consisting of, or consisting essentially of the following steps: extruding a polymer (without any filler, additive, or plasticizer) to form a non-porous precursor film; and stretching the precursor film to form pores, among other things. An exemplary dry stretching process is Dry stretching process. In some embodiments, the extrusion step may include coextrusion, wherein two or more polymer mixtures that may be the same or different from each other are coextruded. In other embodiments, microporous membranes can be prepared by particle stretching (using particle fillers, whose boundaries form crack-shaped micropores when stretched) manufacturing processes and β-nucleated biaxial orientation (BN-BOPP) manufacturing processes. Alternatively, in other embodiments, porous substrates can be manufactured using a wet process (using solvents and fillers), which may involve the use of solvents and / or oils from Celgard Korea Co., Ltd., Japan Asahi Kasei and / or Japan Tonen, which is sometimes referred to as a phase separation or extraction process. Alternatively, in other embodiments, the microporous membrane can be a woven or nonwoven type of membrane. For example, in some embodiments, an electrostatic spinning coating process can be used to form a microporous membrane. The electrostatic spinning process provides a method for coating a polymer composition in the form of nanoscale fibers, and the nanoscale fibers themselves do not need to be porous. The gaps between the fibers provide the necessary openings or pores in the electrospun coating or layer.
[0065] In some embodiments, the microporous membrane can be a monolayer, a bilayer or a multilayer membrane. When used herein, the term "layer" (e.g., in the term "monolayer", "bilayer" or "multilayer") includes a single extrusion or a single cast layer with a thickness of from 2 to 50 microns. The monolayer can be a single extrusion or a single cast layer with a thickness of from 2 to 50 microns. As understood by those skilled in the art, a monolayer is such a layer that is extruded by itself without being extruded with any other layer. Similarly, each of the layers of the coextruded bilayer or multilayer microporous membrane is considered to be a "layer" used herein. The number of layers in the coextruded bilayer will be two, while the number of layers in the coextruded multilayer film will be three or more. The exact number of layers in the bilayer or multilayer coextruded film depends on the die design, and is not necessarily determined by the coextruded material forming the coextruded film. For example, the same material can be used to form each layer in two or three or more layers to form a coextruded bilayer or multilayer film, and even if each layer is made of the same material, these layers will still be considered to be independent layers. In other words, the exact number will be determined by the die design. Each layer of the coextruded bilayer or multilayer film may have a thickness of 0.1 to 20 microns, preferably 0.1 to 5 microns, most preferably 0.1 to 3 microns, 0.1 to 2 microns, 0.1 to 1 micron, 0.1 to 0.9 microns, 0.1 to 0.8 microns, 0.1 to 0.7 microns, 0.1 to 0.6 microns, 0.1 to 0.5 microns, 0.1 to 0.4 microns, 0.1 to 0.3 microns or 0.1 to 0.2 microns. In addition, the monolayer microporous membrane consists of a single extruded or cast layer that is not extruded or cast with any other layer. The monolayer can have a thickness of, for example, from 2 to 50 microns.
[0066] In other embodiments, the microporous membrane can be a double-layer microporous membrane, which is composed of two single extrusion (single extrusion) or casting (single casting) films that have been laminated together, or it is composed of a coextruded double layer, which is made by coextruding two different or identical polymer compositions to form a coextruded film. The total thickness of the double-layer microporous membrane (different from the thickness of each layer constituting the double-layer membrane) can be, for example, 0.2 to 50 microns. The thickness of the two films constituting the double-layer microporous membrane can be from 0.1 to 25 microns. Compared with the method of extrusion plus lamination, the coextrusion method allows the formation of a thinner layer.
[0067] In other embodiments, the microporous membrane can be a multilayer microporous membrane, for example, a membrane comprising three or more layers. The multilayer microporous membrane can be a three-layer, four-layer, five-layer, six-layer, seven-layer, eight-layer, nine-layer or ten-layer membrane. In other embodiments, the membrane may include 11 to 100 layers. The multilayer microporous membrane can be formed by forming [for example, by extruding (such as, single extrusion) or casting (such as, single casting)] three or more monolayers and then laminating them together separately. In these embodiments, the thickness of the multilayer microporous membrane can be from 6 to 100 microns, and the thickness of each layer in the multilayer microporous membrane is from 2 to 30 microns. In other embodiments, the multilayer microporous membrane can be formed by coextruding three or more polymer compositions that can be the same or different. In this embodiment, the thickness of the multilayer microporous membrane can be as thin as 1 micron or as thick as 50 microns. Each layer can have a thickness from 0.1 to 20 microns.
[0068] In other embodiments, a multilayer microporous membrane can be formed by the following combination: a step of forming a single extrusion or single casting layer; a step of coextruding two or more layers; and a lamination step. For example, a single layer can be extruded or cast, and then the two polymer compositions can be extruded to form a coextruded double layer, after which the single layer and the double layer can be laminated together to form a multilayer microporous membrane. In some embodiments, two or three or more coextruded double layers or multiple layers are laminated together to form a multilayer microporous membrane. In some embodiments, a blown film (or bubble) coextrusion method can be used to form a multilayer microporous membrane, wherein the bubble collapses itself. This method can form a multilayer microporous membrane with 2 (double layers), 4, 6, 8, 10, 12 or other even-numbered layers. The method does not form a microporous membrane with 3, 5 (five layers), 7, 9, 11 or other odd-numbered layers.
[0069] For example, the microporous membrane may be a microporous membrane as described in PCT application WO / 2017 / 083633 (the entire contents of which are incorporated herein by reference),
[0070] In the embodiments described herein, lamination may involve applying at least one of heat, pressure, or a combination thereof to connect separate films or layers. Before and / or after lamination, the films or layers used to form the double or multilayer microporous membrane described herein may be subjected to at least one of annealing, MD stretching, TD stretching, calendering, heat setting, and a combination thereof. Alternatively, or additionally, the laminate formed by laminating these films or layers may be subjected to at least one of annealing, MD stretching, TD stretching, calendering, and a combination thereof. In this case, at least one of annealing, MD stretching, TD stretching, and calendering occurs after lamination.
[0071] Unless otherwise specified in a particular embodiment, there are no too many restrictions on the composition of the porous membrane described herein. In some embodiments, the porous membrane can be composed of any extrudable polymer. In some preferred embodiments, the extrudable polymer is a polyolefin, including polyethylene, polypropylene and mixtures thereof.
[0072] In some embodiments, the pores (e.g., nanopores, micropores, or macropores) of the porous membranes described herein can be filled with an ion-conducting medium (ICM). The ICM includes a polymer and a solvent electrolyte. For example, the ICM can include a polymer such as PVDF and an electrolyte. Lithium ions will be conducted in the ICM or liquid electrolyte in the pores. Even if the microporous membrane is not wetted by the electrolyte (is dry), it will conduct ions if the pores are filled with ICM. Microporous membranes with polymers (e.g., polymers from ICM) in the pores have infinite Gurley (10,000 or higher). There are a wide variety of electrolytes, including the following: pure liquid electrolytes---many can be absorbed into the polymer film (Gurley = infinite) to form gel electrolytes, and many can be absorbed into the pores of the porous film (Gurley has a specific value). Batteries with both types of polymer films will work well. In real life, when a liquid electrolyte encounters a polymer, at least a portion of the liquid electrolyte will be absorbed (wet, swell, or gel) into the polymer in some way. Depending on the amount of liquid electrolyte absorbed, we can call it a gel electrolyte or a polymer electrolyte. 100% "pure liquid electrolyte" (which may not often be present in galvanic cells due to polymer absorption of liquid). Our new mathematical definition of ICM tortuosity describes the performance of the layer as a whole.
[0073] like Figure 1 As shown, lithium ion transport in an ion-conducting medium (tending to pass through the solid porous membrane portion within the micropores rather than outside the micropores) is completely different from the flow of a fluid (e.g., a liquid electrolyte fluid) through a porous material such as the porous membrane described herein. The ion-conducting medium does not flow. The tortuosity is the resistivity of the separator membrane (ρ s ) and the resistivity of the electrolyte (ρ e ), as shown by the MacMullin number (Nm) given by the following formula (1), where ε is the porosity.
[0074] (ρ s ) / (ρ e )=N m =τ 2 / ε(1)
[0075] The ion-conducting medium may be at least one of a solid electrolyte, a gel electrolyte, or a liquid electrolyte that absorbs a polymer having infinite Gurley but still capable of transporting ions, and whose τ or tortuosity is always equal to 1. The tortuosity (τ) is represented by the following formula (2):
[0076] τ=L / x(2)
[0077] In equation (2), L is the actual length of the hole, and x is the straight-line distance from one end of the hole to the other. Both L and x are shown in Figure 1 middle.
[0078] Energy battery
[0079] Unless otherwise described in a specific embodiment, there are not many restrictions on the energy cells described herein, and they can be primary or secondary energy cells. For example, in a preferred embodiment, the energy cell is an electrochemical energy cell. The energy cell can also be a primary or secondary cell. As understood by those skilled in the art, a primary cell is a battery designed to be used once, and is not charged and reused like a secondary cell or a rechargeable battery. Typically, the electrochemical reaction in a primary cell is irreversible, while the electrochemical reaction in a secondary cell is reversible. In a preferred embodiment, the energy cell herein is a secondary electrochemical energy cell.
[0080] There are also not many restrictions on the structure of the energy cell. It can include, consist of, or consist essentially of an anode, a cathode, an electrolyte, and a separator. In some embodiments, the energy cell can include, consist of, or consist essentially of an anode, a cathode, and a solid electrolyte. In some embodiments, the energy cell can include, consist of, or consist essentially of an anode, a cathode, a separator, and an electrolyte. The separator can be a separator as described herein.
[0081] In at least one preferred embodiment, the energy cell herein comprises, consists of, or consists essentially of: an anode containing lithium, a cathode, and at least one of an electrolyte and a separator, a solid electrolyte and a separator, or only a solid electrolyte.
[0082] Unless otherwise described in a specific embodiment, there are not many limitations on the material of the anode, and it can be any material known or found to be acceptable as an anode material. In some preferred embodiments, the anode material is a material known or found to be acceptable as an anode material containing lithium. For example, the anode material containing lithium can be at least one selected from the following: lithium cobalt oxide (LCO); lithium manganese oxide (LMO); lithium iron phosphate (LFP); Li(Ni x Mn y Co z)O2), where 0.33>x>0.9 and x+y+z=1; NCA(Li(Ni x Co y Al z )O2), wherein 0.8>x>0.9 and x+y+z=1); and combinations thereof.
[0083] There are also no restrictions on cathode materials, and any material known or found to be acceptable for use as cathode materials can be used. In some preferred embodiments, the cathode comprises at least one material selected from the following: natural graphite, artificial graphite, amorphous carbon, an alloy containing tin and / or silicon, spinel lithium titanium oxide, and combinations thereof.
[0084] Unless otherwise described in a specific embodiment, there are not many limitations on the thickness of the anode. In some preferred embodiments, the thickness of the anode is from about 50 to about 200 microns, from about 55 to 200 microns, from about 60 to 200 microns, from about 65 to 200 microns, from about 70 to 200 microns, from about 75 to 200 microns, from about 80 to 200 microns, from about 85 to 200 microns, from about 90 to 200 microns, from about 90 to 200 microns, from about 100 to 200 microns, from about 105 to 200 microns, from about 110 to 200 microns, from about 120 to 200 microns, from about 140 to 200 microns, from about 150 to 200 microns, from about 160 to 200 microns, from about 170 to 200 microns, from about 180 to 200 microns, from about 190 to 200 microns, from about 200 to 200 microns, from about 210 to 200 microns, from about 220 to 200 microns, from about 230 to 200 microns, from about 240 to 200 microns, from about 250 to 200 microns, from about 260 to 200 microns, from about 270 to 200 microns, from about 280 to 200 microns, from about 290 to 200 microns, from about 300 to 200 microns, from about 310 to 200 microns, from about 320 to 200 microns, from about 330 to 200 microns, from about 350 to 200 In some preferred embodiments, the anode thickness is from about 61 microns or more. In some preferred embodiments, the thickness is about 90 microns or more. In other preferred embodiments, the thickness is from about 122 microns or more. See. Fig.19 , which shows that when the electrode thickness is about 61 microns or more, about 90 microns or more, or about 122 microns or more, lithium deposition does not begin even when charged above 3.5C (1C=2.3mA / cm2). In some embodiments, Li deposition can be avoided even at a charge rate of 5.0C or more, 6.0C or more, 7.0C or more, 8.0C or more, or 9.0C or more. When referring to the thickness of the anode, the word "about" means ±5 microns.
[0085] There are not many restrictions on the thickness of the cathode. The thickness of the cathode is from about 50 to about 200 microns, from about 60 to 200 microns, from about 70 to 200 microns, from about 80 to 200 microns, from about 90 to 200 microns, from about 100 to 200 microns, from about 110 to 200 microns, from about 120 to 200 microns, from about 130 to 200 microns, from about 140 to 200 microns, from about 150 to 200 microns, from about 160 to 200 microns, from about 170 to 200 microns, from about 180 to 200 microns or from about 190 to 200 microns. In some preferred embodiments, the thickness of the cathode can be about 74 microns or more, about 111 microns or more, or about 148 microns or more. See Fig.19 , which shows that when the electrode thickness is about 74 microns or more, about 111 microns or more, or about 148 microns or more, even at temperatures above 3.5C (1C = 2.3 mA / cm 2 ) charging, lithium deposition will not begin. In some embodiments, Li deposition can be avoided even at a charging rate of 5.0C or higher, 6.0C or higher, 7.0C or higher, 8.0C or higher, or 9.0C or higher. When referring to the thickness of the cathode, the word "about" means ± 5 microns.
[0086] Thickness and Lithium Deposition During Charging (Safety) Thickness and galvanic cell rate capability Constant charge capacity, similar discharge and charge kinetics. Focus on charge kinetics. Note that for a given electrochemical system, fixed chemistry, particle size of the material, and other additives, we assume that the effective electrochemical reaction area is relatively fixed. Fig.17 A 4C charging rate system for electrode thicknesses IX and 2X at the starting state (t=0) is shown. Fig.18 A 4C charging rate system for electrode thicknesses 1X and 2X in a dynamic regime (t>0) is shown.
[0087] Unless otherwise described in a particular embodiment, there are not many limitations on the porosity of the anode. In some embodiments, it is about 15% (0.15) or higher; in some embodiments, it is about 20% (0.2) or higher; in some preferred embodiments, it is about 30% (0.3) or higher; and in some even more preferred embodiments, it is about 40% (0.4) or higher. When referring to the anode porosity, the word "about" means ±5%. For example Fig. 20As shown, when the anode porosity is about 15% or more, about 20% or more, about 30% or more, or about 40% or more, lithium deposition may not begin in the primary cell even when the charging rate is equal to or greater than 3.0C. In some embodiments, lithium deposition may not begin even when the charging rate is equal to or greater than 3.5C, 4.0C, 4.5C, 5.0C, 6.0C, 7.0C, or more. Fig. 20 In the experiments, the thickness of the electrodes was varied so that each example had the same amount of active material, so this variable did not affect the results.
[0088] There are also no limitations on the porosity of the cathode. In some embodiments, it is about 10% (0.1) or higher; or in preferred embodiments, about 15% (0.15) or higher, about 20% (0.20) or higher, or about 30% (0.3) or higher. When referring to the cathode porosity, the word "about" means ±5%. For example Fig. 20 As shown, when the cathode porosity is about 10% or more, about 15% or more, about 20% or more, or about 30% or more, lithium deposition may not begin in the primary cell even when the charging rate is equal to or greater than 3.5C. In some embodiments, lithium deposition may not begin even at a charging rate equal to or greater than 3.5C, 4.0C, 4.5C, 5.0C, 6.0C, 7.0C, or more. Fig. 20 In the experiments, the thickness of the electrodes was varied so that each example had the same amount of active material, so this variable did not affect the results.
[0089] Unless otherwise described in a particular embodiment, there are not many limitations on the curvature of the anode. In some preferred embodiments, the curvature of the anode is about 1.2 or less, about 1.3 or less, about 1.5 or less, or about 1.7 or less. In some embodiments, the curvature of the anode is 1.0 or more and 2.0 or less. In some preferred embodiments, the curvature of the anode is from about 1.0 to about 1.3 or from 1.0 to 1.3. When referring to the curvature of the anode, "about" means ±0.2. As Fig.21 As shown, when the anode curvature is between 1.0 and 1.3, lithium deposition does not start in the original battery even when the charging rate is equal to or greater than 3.5 C. When the curvature is between 1.0 and 1.7, lithium deposition does not start in the battery even when the charging rate is equal to or greater than 3.0 C. In some embodiments, lithium deposition may not start even if the charging rate is greater than 4.0 C, 4.5 C, 5.0 C, 6.0 C, or 7.0 C.
[0090] Likewise, unless otherwise described in a particular embodiment, there are not many limitations on the curvature of the cathode. In some preferred embodiments, the cathode curvature is about 1.7 or less, about 1.5 or less, about 1.3 or less, or about 1.2 or less. The cathode curvature can be as low as 1.0 or as high as about 2.0. In some preferred embodiments, the cathode curvature is between about 1.0 and about 1.5 or between about 1.2 and about 2.5. When referring to the cathode curvature, "about" means ±0.2. As Fig.21 As shown in , when the anode curvature is between 1.0 and 1.3, lithium deposition does not start in the original cell even when the charging rate is equal to or greater than 3.5C. When the curvature is between 1.0 and 1.7, lithium deposition does not start in the battery even when the charging rate is equal to or greater than 3.0C. In some embodiments, lithium deposition may not start even if the charging rate is greater than 4.0C, 4.5C, 5.0C, 6.0C, or 7.0C.
[0091] Anode and cathode materials are as described above. In some preferred embodiments, anode and cathode materials are combined with a binder to form anode and cathode. Unless otherwise described in a specific embodiment, there are not many restrictions on the relative content of anode or cathode materials and binder in this combination. In some preferred embodiments, the amount of active material (i.e., cathode or anode material) is from 80wt.% to 99.9wt.%. In some preferred embodiments, the amount is from 90 to 99.9wt.%, and in some other preferred embodiments, the amount is from 95 to 99.9wt.%.
[0092] exist Fig. 22 In the present invention, an exemplary primary battery according to the present disclosure is provided.
[0093] In addition to an anode and a cathode, the energy cell herein may also comprise an electrolyte or an electrolyte and a separator.
[0094] Unless otherwise described in a specific embodiment, there are not too many restrictions on the separator, which can be any separator described herein. Unless otherwise described in a specific embodiment, there are not too many restrictions on the electrolyte, which can be any electrolyte known or found to be useful in a primary or secondary energy battery. In some preferred embodiments, the electrolyte can be selected from: ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC) and combinations thereof.
[0095] In some embodiments, the electrolyte may include an electrolyte additive added thereto.
[0096] As long as the electrolyte is consistent with the objectives described herein, there are not many restrictions on the electrolyte additives described herein. The electrolyte additive can be any additive that is commonly added by battery manufacturers, especially lithium battery manufacturers, to improve battery performance. For example, the exemplary electrolyte additives disclosed in "A Review of Electrolyte Additives for Lithium-ion Batteries" (Power Sources, Vol. 162, No. 2, 2006, pp. 1379-1394), the entire contents of which are incorporated herein by reference. In some preferred embodiments, the electrolyte additive is selected from at least one of the following: SEI improver, cathode protector, flame retardant additive, LiPF6 salt stabilizer, overcharge protector, aluminum corrosion inhibitor, lithium deposition agent or improver or solvation promoter, aluminum corrosion inhibitor, wetting agent and viscosity improver. In some embodiments, the additive may have more than one property, for example, it may be a wetting agent and a viscosity improver.
[0097] Exemplary SEI improvers include VEC (vinyl ethylene carbonate), VC (vinylene carbonate), FEC (fluoroethylene carbonate), LiBOB (lithium bis(lithium oxalate) borate). Exemplary cathode protectors include N,N'-dicyclohexylcarbodiimide, N,N-diethylaminotrimethylsilane, LiBOB. Exemplary flame retardant additives include TTFP (tris(2,2,2-trifluoroethyl)phosphate), fluorinated propylene carbonate, MFE (methyl nonafluorobutyl methyl ether). Exemplary LiPF6 salt stabilizers include LiF, TTFP (tris(2,2,2-trifluoroethyl)phosphite), 1-methyl-2-pyrrolidone, fluorinated carbamate, hexamethylphosphoramide. Exemplary overcharge protectors include xylene, cyclohexylbenzene, biphenyl, 2,2-diphenylpropane, tert-butyl phenyl carbonate. Exemplary Li deposition improvers include AlI3, SnI2, hexadecyltrimethylammonium chloride, perfluoropolyether, tetraalkylammonium chloride with long alkyl chains. Exemplary ion rescue enhancers include 12-crown-4, TPFPB (tris(pentafluorophenyl)). Exemplary aluminum corrosion inhibitors include LiBOB, LiODFB, such as borates. Exemplary wetting agents and viscosity diluents include cyclohexane and P2O5.
[0098] Anode or cathode
[0099] Unless otherwise described in a specific embodiment, there are not many limitations on the anodes or cathodes described herein, and they may be similar to those incorporated into the energy cells described herein. However, the anodes and cathodes described under this heading are not incorporated into energy cells, but they may be used in the future.
[0100] Complex, vehicle or equipment
[0101] A composite comprising a battery separator as described herein and one or more electrodes, such as an anode, a cathode, or an anode and a cathode, the electrode being arranged to be in direct contact with the separator. There are not many restrictions on the type of electrode. For example, the electrode can be those suitable for lithium ion secondary batteries.
[0102] Suitable anodes may have an energy capacity greater than or equal to 372 mAh / g, preferably ≥700 mAh / g, and most preferably ≥1000 mAH / g. The anode is composed of lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy) or a mixture of lithium metal and / or lithium alloy and materials such as carbon (e.g., coke, graphite), nickel, copper. The anode is not made solely of lithium-containing intercalation compounds or lithium-containing insertion compounds.
[0103] Suitable cathodes may be any cathode that is compatible with the anode and may include intercalation compounds, insertion compounds, or electrochemically active polymers. Suitable intercalation materials include, for example, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMn2O4, V6O 13 , V2O5 and CuCl2. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline and polythiophene.
[0104] Any separator, energy cell, or anode or cathode described herein can be used in any vehicle (eg, an electric car) or device (eg, a cell phone or laptop computer) that is fully or partially powered by a battery.
[0105] According to at least selected embodiments, aspects or purposes, the present disclosure or invention may provide or be directed to new or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, manufacturing and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems and / or the like for lithium batteries (especially secondary lithium batteries, such as secondary lithium ion batteries) and / or CE, ESS and / or EDV batteries. According to at least specific embodiments, the present disclosure or invention is directed to new or improved methods of observing or defining tortuosity, porosity, lithium deposition and galvanic cell design using such new ideas, definitions and / or data. In addition, disclosed herein are methods, systems and battery components for extending battery life, reducing battery failure, reducing dendrites, reducing lithium deposition, maintaining charge and discharge rates, improved configurations, improved performance and / or the like.
[0106] According to at least selected embodiments, aspects or purposes, the present disclosure or invention may provide or be directed to new or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, making and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems and / or the like for lithium batteries (especially secondary lithium batteries, such as secondary lithium ion batteries) and / or CE, ESS and / or EDV batteries, for example, including:
[0107] An improved porous membrane or battery separator comprising a porous membrane having at least one of the following properties when wetted by an electrolyte:
[0108] No volume or small volume;
[0109] Massless or lightweight; absorbs as much liquid electrolyte as possible;
[0110] Block or remove any harmful substances in the electrolyte;
[0111] Does not melt at any high temperature;
[0112] Does not react with the cathode or anode under any conditions;
[0113] Have mechanical strength equal to or greater than that of steel;
[0114] It is an electrical insulator in all circumstances;
[0115] Preventing metal dendrite growth
[0116] The battery separator described above, wherein the separator has no volume or low volume when wetted by the electrolyte.
[0117] The battery separator described above, wherein the separator is massless or lightweight when wetted by the electrolyte.
[0118] The battery separator described above, wherein, when wetted by the electrolyte, the separator absorbs as much liquid electrolyte as possible.
[0119] The battery separator described above, wherein the separator inhibits dendrites when wetted by the electrolyte.
[0120] The battery separator described above, wherein the separator does not melt at any elevated temperature when wetted by the electrolyte.
[0121] The battery separator described above, wherein, when wetted by the electrolyte, the separator does not react with the cathode or anode under any conditions.
[0122] The battery separator described above, wherein the separator has a mechanical strength equal to or greater than steel when wetted by electrolyte.
[0123] The battery separator described above, wherein the separator is in any case an electrical insulator when wetted by the electrolyte.
[0124] The battery separator described above, wherein the separator inhibits metal dendrite growth when wetted by the electrolyte.
[0125] The battery separator described above, wherein the separator has at least two of these characteristics.
[0126] The battery separator described above, wherein the separator has at least three of these characteristics.
[0127] The battery separator described above, wherein the separator has at least four of these characteristics.
[0128] The battery separator described above, wherein the separator has at least five of these properties.
[0129] The battery separator described above, wherein the separator has at least six of these characteristics.
[0130] The battery separator described above, wherein the separator has at least seven of these properties.
[0131] The battery separator described above, wherein the separator has at least eight of these properties.
[0132] The battery separator described above, wherein the separator has at least nine of these properties.
[0133] The battery separator described above, wherein the battery separator is macroporous, microporous or nanoporous, and the pores are filled with an ion-conducting medium.
[0134] The battery separator as described above, wherein the separator conducts lithium ions when dry (without electrolyte) and / or when wetted with electrolyte.
[0135] The battery separator as described above, wherein the separator has an infinite Gurley value.
[0136] The battery separator as described above, wherein the separator has an infinite Gurley value.
[0137] A device capable of operating at a temperature greater than or equal to 3.0C (1C = 2.3 mA / cm 2 ) without lithium deposition, the energy cell comprising:
[0138] an anode comprising lithium; and
[0139] cathode
[0140] The above-mentioned energy primary battery, wherein the charging rate is greater than or equal to 3.5C.
[0141] The above-mentioned energy primary battery, wherein the charging rate is greater than or equal to 4.0C.
[0142] The above-mentioned energy primary battery, wherein the charging rate is equal to or greater than 4.5C.
[0143] The above-mentioned energy primary battery, wherein the charging rate is equal to or greater than 3.0C, but less than 5.0C.
[0144] The above-mentioned energy cell, wherein the thickness of the anode is from about 50 to about 200 microns.
[0145] The above-mentioned energy cell, wherein the thickness of the anode is from about 60 to about 200 microns.
[0146] The above-mentioned energy cell, wherein the thickness of the anode is from about 60 to about 125 microns.
[0147] The above-mentioned energy cell, wherein the thickness of the cathode is from about 50 to about 200 microns.
[0148] The above-mentioned energy cell, wherein the thickness of the cathode is from about 75 to about 200 microns.
[0149] The above-mentioned energy cell, wherein the thickness of the cathode is from about 75 to about 150 microns.
[0150] The above energy cell, wherein the anode porosity is greater than or equal to 15%.
[0151] The above energy cell, wherein the anode porosity is greater than or equal to 20%.
[0152] The above energy cell, wherein the anode porosity is greater than or equal to 30%.
[0153] The above energy cell, wherein the anode porosity is greater than or equal to 40%.
[0154] The above energy cell, wherein the anode porosity is greater than or equal to 15%, but less than or equal to 50%.
[0155] The above energy cell, wherein the cathode porosity is greater than or equal to 10%.
[0156] The above energy cell, wherein the cathode porosity is greater than or equal to 15%.
[0157] The above energy cell, wherein the cathode porosity is greater than or equal to 20%.
[0158] The above energy cell, wherein the cathode porosity is greater than or equal to 30%.
[0159] The above energy cell, wherein the cathode porosity is greater than or equal to 10%, but less than 40%.
[0160] The above-mentioned energy battery, wherein the anode curvature is less than or equal to 2.0.
[0161] The above-mentioned energy battery, wherein the anode curvature is less than or equal to 1.7.
[0162] The above-mentioned energy battery, wherein the curvature of the anode is less than or equal to 1.5.
[0163] The above-mentioned energy battery, wherein the curvature of the anode is less than or equal to 1.3.
[0164] The above-mentioned energy battery, wherein the curvature of the anode is less than or equal to 1.2.
[0165] The above-mentioned energy battery, wherein the anode curvature is greater than or equal to 1.2 and less than or equal to 1.3.
[0166] The above-mentioned energy battery, wherein the cathode curvature is less than or equal to 2.0.
[0167] The above-mentioned energy battery, wherein the cathode curvature is less than or equal to 1.7.
[0168] The above-mentioned energy battery, wherein the cathode curvature is less than or equal to 1.5.
[0169] The above-mentioned energy battery, wherein the cathode curvature is less than or equal to 1.3.
[0170] The above-mentioned energy battery, wherein the cathode curvature is less than or equal to 1.2.
[0171] The above-mentioned energy battery, wherein the cathode curvature is greater than or equal to 1.2 and less than or equal to 1.5.
[0172] The above energy battery, wherein the anode containing lithium is selected from: lithium cobalt oxide (LCO); lithium manganese oxide (LMO); lithium iron phosphate (LFP); Li (Ni x Mn y Co z )O2), where 0.33>x>0.9 and x+y+z=1; NCA(Li(Ni x Co y Al z )O2), wherein 0.8>x>0.9 and x+y+z=1; and at least one material selected from combinations thereof.
[0173] The above energy cell, wherein the cathode comprises at least one material selected from the following: natural graphite, artificial graphite, amorphous carbon, alloys containing tin and / or silicon, spinel lithium titanium oxide and combinations thereof.
[0174] The above energy cell also contains an electrolyte.
[0175] In the above energy battery, the electrolyte is selected from: ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC) and combinations thereof.
[0176] The above energy cell, wherein the electrolyte includes an electrolyte additive.
[0177] The above energy cell also includes the above membrane or battery separator.
[0178] An anode comprises lithium.
[0179] The anode has a thickness of about 50 to about 200 microns.
[0180] The anode as described above, wherein the thickness of the anode is from about 60 to about 200 microns.
[0181] The anode as described above, wherein the thickness of the anode is from about 60 to about 125 microns.
[0182] The above-mentioned anode, wherein the anode porosity is greater than or equal to 15%.
[0183] The above-mentioned anode, wherein the anode porosity is greater than or equal to 20%.
[0184] The above-mentioned anode, wherein the anode porosity is greater than or equal to 30%.
[0185] The above-mentioned anode, wherein the anode porosity is greater than or equal to 40%.
[0186] The above anode, wherein the anode porosity is greater than or equal to 15%, but less than or equal to 50%.
[0187] The above-mentioned anode, wherein the anode curvature is less than or equal to 2.0.
[0188] The above-mentioned anode, wherein the anode curvature is less than or equal to 1.7.
[0189] The above-mentioned anode, wherein the anode curvature is less than or equal to 1.5.
[0190] The above-mentioned anode, wherein the anode curvature is less than or equal to 1.3.
[0191] The above-mentioned anode, wherein the anode curvature is less than or equal to 1.2.
[0192] The above-mentioned anode, wherein the anode curvature is greater than or equal to 1.0 and less than or equal to 2.0.
[0193] The above-mentioned anode, wherein the anode curvature is greater than or equal to 1.2 and less than or equal to 1.3.
[0194] A cathode.
[0195] The cathode as above, wherein the thickness of the cathode is from about 50 to about 200 microns.
[0196] The cathode as above, wherein the thickness of the cathode is from about 75 to about 200 microns.
[0197] The cathode as above, wherein the thickness of the cathode is from about 75 to about 150 microns.
[0198] The cathode described above, wherein the cathode porosity is greater than or equal to 10%.
[0199] The cathode described above, wherein the cathode porosity is greater than or equal to 15%.
[0200] The cathode described above, wherein the cathode porosity is greater than or equal to 20%.
[0201] The cathode described above, wherein the cathode porosity is greater than or equal to 30%.
[0202] The cathode described above, wherein the cathode porosity is greater than or equal to 10% but less than 40%.
[0203] The above-mentioned cathode, wherein the cathode curvature is less than or equal to 2.0.
[0204] The above-mentioned cathode, wherein the cathode curvature is less than or equal to 1.7.
[0205] The above-mentioned cathode, wherein the cathode curvature is less than or equal to 1.5.
[0206] The above-mentioned cathode, wherein the cathode curvature is less than or equal to 1.3.
[0207] The above cathode, wherein the cathode curvature is less than or equal to 1.2.
[0208] The above-mentioned cathode, wherein the cathode curvature is greater than or equal to 1.2 and less than or equal to 1.5.
[0209] The lithium-containing anode, wherein the lithium-containing anode comprises at least one material selected from the following: lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), (Li(Ni x Mn y Co z )O2) (where 0.33>x>0.9 and x+y+z=1), NCA(Li(Ni x Co y Al z )O2) (wherein 0.8>x>0.9 and x+y+z=1) and combinations thereof.
[0210] The cathode described above, wherein the cathode comprises at least one material selected from the following: natural graphite, artificial graphite, amorphous carbon, an alloy containing tin and / or silicon, spinel lithium titanium oxide, and combinations thereof.
[0211] New or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, manufacturing and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems and / or the like for lithium batteries (especially secondary lithium batteries, such as secondary lithium ion batteries) and / or CE, ESS and / or EDV batteries; new or improved methods of observing or defining tortuosity, porosity, lithium deposition and galvanic cell design using such new ideas, definitions and / or data; new or improved methods, systems and battery components for extending battery life, reducing battery failure, reducing dendrites, reducing lithium deposition, maintaining charge and discharge rates, improved configurations, improved performance and / or combinations thereof; and / or the like as shown, described or claimed herein.
[0212] According to at least selected embodiments, the present disclosure or invention is directed to new or improved separators, battery separators, electrodes, cathodes, anodes, batteries, galvanic cells, systems; and / or methods of designing, understanding, manufacturing and / or using such separators, battery separators, electrodes, cathodes, anodes, galvanic cells, systems and / or the like for lithium batteries (especially secondary lithium batteries, such as secondary lithium ion batteries) and / or CE, ESS and / or EDV batteries. According to at least specific embodiments, the present disclosure or invention is directed to new or improved methods of observing or defining tortuosity, porosity, lithium deposition and galvanic cell design using such new ideas, definitions and / or data. In addition, disclosed herein are methods, systems and battery components for extending battery life, reducing battery failure, reducing dendrites, reducing lithium deposition, maintaining charge and discharge rates, improved configurations, improved performance and / or the like.
[0213] According to at least certain embodiments, disclosed herein is an improved battery separator comprising a porous membrane having at least one of the following properties when wetted by an electrolyte: no volume or low volume; no mass or light mass; absorbing as much liquid electrolyte as possible; blocking or removing any harmful substances in the electrolyte; not melting at any high temperature; not reacting with the cathode or anode under any conditions; having a mechanical strength equal to or greater than that of steel; being an electrical insulator under any circumstances; preventing metal dendrite growth. Also disclosed herein is an energy cell in which lithium deposition does not occur even at high charging rates. The energy cell may comprise the improved separator disclosed herein. The energy cell also includes an anode containing lithium and a cathode containing a carbonaceous material (in some embodiments). Also disclosed herein are anodes and cathodes separated from the energy cell, but they can be used in the energy cell disclosed herein.
[0214] The foregoing written description of the structure and method is presented for illustrative purposes only. The embodiments are used to disclose exemplary embodiments including the best mode, and also enable any person skilled in the art to practice the invention, including making and using any device or system and performing any associated method. These embodiments are not intended to be exhaustive or limit the invention to the precise steps and / or forms disclosed, and many modifications and changes are possible in accordance with the above teachings. The features described herein can be combined in any combination. The steps of the method described herein can be performed in any order that is physically feasible. The patentable scope of the present invention is defined by the appended claims and may include other embodiments that occur to those skilled in the art. If such other embodiments have structural elements that are indistinguishable from the literal language of the claims, or if they include equivalent structural elements that are not substantially different from the literal language of the claims, they are intended to be within the scope of the claims.
[0215] The compositions and methods of the appended claims are not limited to the scope of the specific compositions and methods described herein, which are intended to serve as illustrations of several aspects of the claims. Any compositions and methods that are functionally equivalent are intended to fall within the scope of the claims. Various modifications of the compositions and methods, in addition to those shown and described herein, are also intended to fall within the scope of the appended claims. In addition, although only specific representative compositions and method steps disclosed herein are specifically described, other combinations of compositions and method steps are also intended to fall within the scope of the appended claims, even if not specifically described. Therefore, combinations of steps, elements, components, or components may be explicitly or less explicitly mentioned herein, but other combinations of steps, elements, components, and components are also included even if not explicitly stated.
[0216] When used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from a particular value and / or to another particular value. Similarly, when a numerical value is expressed as an approximation by using the antecedent "about", it should be understood that the particular value forms another embodiment. It should be further understood that the endpoints of each range are important in relationship to the other endpoints and are independent of the other endpoints. "Optional" or "optionally" means that the event or situation described subsequently may or may not occur, and the description includes instances where the event or situation occurs and instances where it does not occur.
[0217] Throughout the specification and claims of this specification, the word "comprising" and variations of the word, such as "participle form comprising" and "singular form comprising", mean "including but not limited to", and are not intended to exclude, for example, other additives, components, integers or steps. The terms "consisting essentially of" and "consisting of" can be used in place of "comprising" and "including" to provide more specific embodiments of the present invention, and they are also disclosed. "Exemplary" means "an example of..." and is not intended to convey the meaning of being a preferred or ideal embodiment. "Such as" is not used in a restrictive sense, but is used for illustration or exemplary purposes.
[0218] Except where otherwise noted, all numbers indicating geometric shapes, dimensions, and the like used in the specification and claims should at least be understood as not attempting to limit the application of the doctrine of equivalents to the scope of the claims and should be interpreted in light of the number of significant digits and ordinary rounding techniques.
[0219] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the disclosed invention belongs.Publications cited herein and the materials they cite are expressly incorporated herein by reference.
[0220] Furthermore, the invention illustratively disclosed herein suitably may be practiced in the absence of any element not specifically disclosed herein.
Claims
1. A battery separator comprising a dry process porous membrane; the dry process porous membrane comprises a coextruded multilayer, each layer having a thickness between 0.1 and 0.9 microns, and the average pore size of the dry process porous membrane relative to the thickness is up to 1 micron; at least one of the multilayers is a ceramic coating comprising a mixture of polyolefin and ceramic, or at least one of the multilayers is a pure ceramic coating; The micropores of the porous membrane are filled with an ion-conducting medium (ICM), which contains a polymer and a solvent electrolyte, has infinite Gurley, does not flow, and the curvature of ion conduction becomes always 1, so that the resistivity of the porous membrane is greater than the resistivity of the solvent electrolyte, ensuring that lithium ions tend to migrate along the ICM filled with micropores, and more tend to migrate along the solvent electrolyte in the micropores; the porous membrane conducts lithium ions even when it is not wetted by the electrolyte; even at high charging rates, lithium deposition no longer occurs in lithium-ion batteries or primary batteries.
2. The battery separator according to claim 1, wherein The separator has a JIS Gurley value of 10,000 or more; or, the ion conductive medium is selected from: a polymer-imbibed solid electrolyte, a polymer-imbibed gel electrolyte, or a polymer-imbibed liquid electrolyte.
3. The battery separator according to claim 1 or 2, wherein: The battery separator has at least one of the following: The pores of the battery separator include macropores, micropores or nanopores, and at least a portion of the pores are filled with an ion-conducting medium; The separator conducts lithium ions when dry (without electrolyte) and / or wetted with electrolyte.
4. An energy cell, wherein: The energy cell has a lithium-containing anode; the anode is composed of lithium metal foil, lithium alloy foil (such as lithium aluminum alloy), a mixture of lithium metal and / or lithium alloy, preferably containing carbon (such as coke, graphite), nickel, and copper; the anode is not made only of lithium-containing intercalation compounds or lithium-containing insertion compounds; in this way, lithium deposition no longer occurs in lithium-ion batteries or primary cells even at high charging rates.
5. The energy cell according to claim 4, wherein: The anode comprises at least one material selected from the following: Lithium cobalt oxide (LCO); lithium manganese oxide (LMO); lithium iron phosphate (LFP); Li(Ni x Mn y Co z )O2, where 0.33>x>0.9 and x+y+z=1; NCA[Li(Ni x Co y Al z )O2], where 0.8>x>0.9 and x+y+z=1.
6. The energy cell according to claim 4, having at least one of the following: The micropores of the battery separator of the energy cell are filled with ICM; The cathode thickness of the energy cell is from 50 to 200 microns, the cathode porosity is greater than or equal to 10% but less than 40%, and the cathode curvature is greater than or equal to 1.2 and less than or equal to 1.5; The anode thickness of the energy cell is from 50 to 200 microns, the anode porosity is greater than or equal to 15% but less than or equal to 50%, and the anode curvature is greater than or equal to 1.2 and less than or equal to 1.3; The charging rate of the energy battery is greater than or equal to 3.0C (1C = 2.3mA / cm 2 ), greater than or equal to 3.5C, greater than or equal to 4.0C, or greater than or equal to 4.5C but less than 5.0C; The thickness of the anode is from 60 to 200 microns, or from 60 to 125 microns; The thickness of the cathode is from 75 to 200 microns, or from 75 to 150 microns; The anode porosity is greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 40%; The cathode porosity is greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, or greater than or equal to 30%; The anode curvature is less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2; The cathode curvature is less than or equal to 2.0, less than or equal to 1.7, less than or equal to 1.5, less than or equal to 1.3, or less than or equal to 1.2; The cathode comprises at least one material selected from the group consisting of natural graphite, artificial graphite, amorphous carbon, an alloy containing tin and / or silicon, spinel lithium titanium oxide, and combinations thereof; Further comprising an electrolyte; the electrolyte is selected from: ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC); and combinations thereof; and The electrolyte includes an electrolyte additive.
7. The energy cell according to any one of claims 4 to 6, having at least one of the following: The thickness of the anode is 50 to 200 microns, 60 to 200 microns, or 60 to 125 microns; The anode porosity is greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 30%, or greater than or equal to 40%, but less than or equal to 50%; The anode curvature is 2.0 or less, 1.7 or less, 1.5 or less, 1.3 or less, or 1.2 or less; and The anode curvature is greater than or equal to 1.0 and less than or equal to 2.0, or greater than or equal to 1.2 and less than or equal to 1.
3.
8. The energy cell as claimed in any one of claims 4 to 6, comprising or included in a secondary lithium battery.
9. A lithium battery or a lithium primary battery, wherein: The invention comprises the battery separator according to any one of claims 1 to 3.
10. A method for preventing lithium deposition in lithium batteries, forcing lithium ions to migrate through the micropores of a battery separator filled with ICM, comprising at least one of the following measures: making the average pore size of a dry porous membrane of a battery separator larger than its thickness; adding a pure ceramic coating, or adding a mixed ceramic coating of polyolefin and ceramic; filling the micropores of the porous membrane with an ion conductive medium (ICM), wherein the ICM comprises a polymer and a solvent electrolyte, has infinite Gurley, does not flow, and the curvature of ion conduction always becomes 1; making the resistivity of the porous membrane greater than the resistivity of the solvent electrolyte, so that lithium ions tend to continue to migrate along the ICM that fills the micropores, and more tend to continue to migrate along the solvent electrolyte in the micropores.
